On Negatively Skewed Extended Generalized Logistic Distribution - Olapade, A. K. (2014)
In this paper, we considered a form of generalized logistic distribution which is call negatively skewed extended generalized logistic distribution or extended type I1 generalized logistic distribution. Some theorems that relate the distribution to some other statistical distributions are established. A possible application of one of the theorems is included.